Preventing Alzheimer's: Our Most Urgent Health Care Priority. Issue 5 (September 2019) - Sherzai, Dean; Sherzai, Ayesha
Dementia is the fastest growing epidemic in the developed nations, and if not curtailed, it will single handedly collapse our health care system. The prevalence of dementia is 1 in 10 individuals older than 65 years and increases to 50% of all individuals older than 85 years. The prevalence of Alzheimer's dementia (AD), the most common form of dementia, has been increasing rapidly and is projected to reach 16 million individuals by the year 2050. Several prevailing myths about the science of dementia are discussed, such as that AD is inevitable and that it is exclusively a genetic disease. The fact is that AD is dependent on a multitude of genetic, epigenetic, and environmental factors that interact with one another. In fact, 4 core drivers represent 90% of what determines disease progression in AD. These are (1) glucose or energy dysregulation, (2) lipid dysregulation, (3) inflammation, and (4) oxidation. Lifestyle change can significantly alter the course of AD. The authors have created an acronym—NEURO—to help lifestyle practitioners and the public remember the most important lifestyle elements in the treatment and prevention of AD based on the evidence. "N" is for Nutrition, "E" for Exercise, "U" for Unwind (stress management), "R" for Restorative Sleep, and "O" for Optimizing mental and social activity. The evidence base for each of the components is reviewed.